2016
DOI: 10.1155/2016/8314040
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous Sinus Thrombosis during Everest Expedition: A Case Report and Review of the Literature

Abstract: Cerebral venous sinus thrombosis (CVST) is a rare but serious disorder that is associated with a poor clinical outcome. We report a 35-year-old man who had a severe headache and diplopia while climbing Mount Everest. His MR venography showed right transverse and right sigmoid sinus thrombosis. He improved on anticoagulant and symptomatic measures. Cerebral venous sinus thrombosis at high altitude is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Furthermore, structural obstruction of the cerebral venous sinuses include traumatic compression, direct injury due to fractures or compression from mass lesions including tumors, arteriovenous malformations, and dural arteriovenous fistulae [12-14]. This gender-ratio is reversed at high altitude [5-7]. While this observation was reported in single case reports or small case series, our study confirms this phenomenon in the yet largest published series of 21 patients.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, structural obstruction of the cerebral venous sinuses include traumatic compression, direct injury due to fractures or compression from mass lesions including tumors, arteriovenous malformations, and dural arteriovenous fistulae [12-14]. This gender-ratio is reversed at high altitude [5-7]. While this observation was reported in single case reports or small case series, our study confirms this phenomenon in the yet largest published series of 21 patients.…”
Section: Discussionsupporting
confidence: 75%
“…Nepal is one of the few countries in the world with a higher average altitude (10,000 ft). Increased incidence of CVT has been associated with high elevation [5-7], and strenuous activity at peak summits [6,8-11]. Most of the reports reported an increased incidence of CVT in men at high altitude.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors reported CVT at extreme HA [>7200 towards Cho Oyu (8201 m), >5000 m towards Gasherbrum I (8068 m), Mount Everest at 8848 m and at 8511 m] with a length of stay ranging from 20 to 45 days. 66 , 74 - 76 Interestingly, while Khanal et al 66 reported the involvement of the right transverse and sigmoid sinus in a subject with low protein S plasma activity, all the other authors reported the involvement of the superior sagittal sinus in subjects without any known risk factors. 74 - 76 Familial thrombophilia (protein S or C deficiency, heterozygous Factor V Leiden mutation) was identified as the cause of few CVT case reports occurred between 3000 and 8848 m asl.…”
Section: Literature and Research Methodsmentioning
confidence: 99%
“…In the present study headache was seen in 94% of patients which was in agreement with previous studies (2,17) . Clinical presentation of CVST is extremely variable, ranging from isolated headache to focal deficits to encephalopathy to psychiatric manifestations to coma (2,8,(18)(19)(20) . Clinical presentation of our cohort is almost identical to what has been reported from the west.…”
Section: Discussionmentioning
confidence: 99%